2021
DOI: 10.3390/antibiotics10030324
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. in Pet Reptiles in Portugal: Prevalence and Chlorhexidine Gluconate Antimicrobial Efficacy

Abstract: A fraction of human Salmonella infections is associated with direct contact with reptiles, yet the number of reptile-associated Salmonellosis cases are believed to be underestimated. Existing data on Salmonella spp. transmission by reptiles in Portugal is extremely scarce. The aim of the present work was to evaluate the prevalence of Salmonella spp. in pet reptiles (snakes, turtles, and lizards), as well as evaluate the isolates’ antimicrobial resistance and virulence profiles, including their ability to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The differences in Salmonella prevalence found in this literature search are similar to those reported previously in a number of individual studies. Specifically, lower detections rates in chelonians in comparison to snakes or lizards have been repeatedly reported ( Geue and Löschner, 2002 ; Scheelings et al, 2011 ; Hydeskov et al, 2013 ; Lukac et al, 2015 ; Corrente et al, 2017 ; Bjelland et al, 2020 ; Cota et al, 2021 ; Zając et al, 2021 ). However, other studies have found a higher prevalence in chelonians ( Ebani et al, 2005 ; Bertelloni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The differences in Salmonella prevalence found in this literature search are similar to those reported previously in a number of individual studies. Specifically, lower detections rates in chelonians in comparison to snakes or lizards have been repeatedly reported ( Geue and Löschner, 2002 ; Scheelings et al, 2011 ; Hydeskov et al, 2013 ; Lukac et al, 2015 ; Corrente et al, 2017 ; Bjelland et al, 2020 ; Cota et al, 2021 ; Zając et al, 2021 ). However, other studies have found a higher prevalence in chelonians ( Ebani et al, 2005 ; Bertelloni et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…The differences noted in detection rates between wild reptiles and reptiles in captivity could—as mentioned above—also be due to differences in conditions, with dietary, stress and crowding-related factors likely causing the higher detection rates found in reptiles in captivity. Given the high dependency of ectothermic organisms on their environment, and natural living situations probably reflecting more physiological conditions than those in captivity, this could contribute to a stronger immune system and reduced stress ( DuPonte et al, 1978 ; Geue and Löschner, 2002 ; Dickinson et al, 2005 ; Scheelings et al, 2011 ; Cota et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…geographic distribution in reptiles, regardless of climate or environment. Including European countries, studies in this area come from Croatia [ 65 ], Italy [ 63 , 66 , 67 ], Spain [ 68 ], Norway [ 31 ], Guadeloupe (French West Indies) [ 59 ], Poland [ 30 , 46 , 69 , 70 ], Portugal [ 71 ] and Slovenia [ 72 ] ( Table 1 ). In Croatia, Salmonella spp.…”
Section: Salmonella Spp Prevalence In Amphibians and Reptilesmentioning
confidence: 99%
“…[12,21]. The close contact between chelonians and humans provides favourable conditions for the transmission of zoonotic infections, with reptile-associated salmonellosis being related to more severe clinical scenarios than those caused by other sources of infection [22][23][24].…”
Section: Introductionmentioning
confidence: 99%